Data Capture of Exergames using Kinect Sensor for Gameplay Analysis - Rauf, Muhammad Fairuz Bin Abd; Ismail, Syahirah; Marjudi, Suziyanti; Amran, Mohd Fahmi Mohamad; Majid, Nur Amlya Abd; Adnan, Zuraidy; Yusop, Nurhafizah Moziyana Mohd (International Journal of Engineering and Technology, 2018)
This project aims to examine Exergames and its data capturing ability. The project tackles on how Exergames' tools are utilized and emphasize Kinect as the best Exergames tools to capture data. The research team developed a prototype application that can collect user information and display the result of their game play. All test conducted are using personal computer and the Kinect sensor. The results should be able to validate that Exergames can gather data and post development can convert those data into useful information for use in specific fields or for use to cater specific users. The result should prove that Kinect-based Exergames can capture useful data and the data can be utilized to maximize Exergames' potential as a new data capture technology alongside other data capture technologies.